K27M-mutant histone-3 as a novel target for glioma immunotherapy - Sahm, Katharina; Ott, Martina; Bunse, Theresa; Sahm, Felix; Bunse, Lukas; Deumelandt, Katrin; Sonner, Jana K.; Keil, Melanie; Deimling, Andreas von; Wick, Wolfgang; Platten, Michael (OncoImmunology, 2017)
Mutation-specific vaccines have become increasingly important in glioma immunotherapy; however, shared neoepitopes are rare. For diffuse gliomas, a driver mutation in the gene for isocitrate dehydrogenase type-1 has been shown to produce an immunogenic epitope currently targeted in clinical trials. For highly aggressive midline gliomas, a recurrent point mutation in the histone-3 gene (H3F3A) causes an amino acid change from lysine to methionine at position 27 (K27M). Here, we demonstrate that a peptide vaccine against K27M-mutant histone-3 is capable of inducing effective, mutation-specific, cytotoxic T-cell- and T-helper-1-cell-mediated immune responses in a major histocompatibility complex (MHC)-humanized mouse model. By proving an immunologically effective presentation of the driver mutation H3K27M on MHC class II in human H3K27M-mutant gliomas, our data provide a basis for the further clinical development of vaccine-based or cell-based immunotherapeutic approaches targeting H3K27M.
Gesehen am 25.04.2018